Pharmacokinetics of cisplatin in an esophageal cancer patient on hemodialysis who was treated with a full-dose cisplatin-fluorouracil regimen: A case report. (October 2019) - Amagai, Hiroyuki; Murakami, Kentaro; Sakata, Haruhito; Uesato, Masaya; Hayano, Koichi; Kano, Masayuki; Fujishiro, Takeshi; Toyozumi, Takeshi; Yoshihide, Senba; Yamamoto, Kohei; Hayashi, Hideki; Matsubara, Hisahiro
Introduction: Cancer patients undergoing hemodialysis might be under-treated because the pharmacokinetics of anti-cancer drugs in such patients remain unknown and out of concern related to the potential development of severe adverse effects. However, patients with chemosensitive cancer, such as esophageal cancer, should receive chemotherapy at a dose that is sufficient to attain a favorable therapeutic effect. We herein present an interesting case involving an esophageal cancer patient who was successfully treated with subtotal thoracic esophagectomy, and adjuvant full-dose chemotherapy with cisplatin and 5-fluorouracil while concomitantly undergoing hemodialysis. We carried out a pharmacokinetics analysis of cisplatin, and also conducted a systematic review on the dose and pharmacokinetics. Case report: A 57-year-old male patient with esophageal cancer who was undergoing hemodialysis was referred to our hospital. He underwent subtotal thoracic esophagectomy. The pathological diagnosis was T1b, N2 (5/26), M0, ly2, v2, stage IIIA (Union for International Cancer Control, 8th edition). Because of the high degree of lymph node metastasis, adjuvant chemotherapy with cisplatin was recommended. Cisplatin (80 mg/m 2 ) was infused intravenously within 30 min on day 1, and 5-fluorouracil (800 mg/m 2 ) was infused continuously on days 1–5 of a 28-day cycle. Thrombocytopenia (grade 3) occurred on day 16, leucopenia (grade 3) occurred on day 23, and anemia (grade 3) occurred on day 30. The onset of hematologic toxicities was prolonged in comparison to patients with a normal renal function.